Structural characterisation of the terminating groups of some polyprenyl phosphates and of rubber from the lactarius mushroom - Sakdapipanich J T; Gou L B; Mekkriengkrai D; Tanaka Y (Journal of Rubber Research, 2001)
A series of trans- and cis-allylic diphosphates were synthesized as model compound of natural rubber and were analysed by NMR techniques. The 1H-NMR spectra of terminal methylene protons of polyprenols linked to mono- and di-phosphates showed a triplet signal. centering around 4.41-4.44 and 4.46-4.49, respectively. The coupling constants of 5.0 Hz-6.0 Hz and 6.0 Hz - 7.0 Hz were observed for trans- and cis-allylic diphosphate groups, respectively. In the alpha-terminal isoprene unit of polyprenols, the cis-and trans-allylic C-4 methylene protons resonate at 4.081 and 4.150, respectively. The alpha C-4 methylene carbon of mono- and di-phosphate groups showed a doublet signal around 61-63 in the 13C-NMR spectrum, the chemical shift value of which decreased with increase the chain-length of polyrenols. The 31P-NMR spectra of mono-and di-phosphate groups showed a signal around 1.5 and -7 to -8, respectively, independent of chain-length and configuration of the allylic compounds. A long-chain polyprenol from Lactarius volemus, composed of about 300 isoprene units, was phosphorylated to analyse the effect of chain length.
Keywords: 13C-NMR; 1H-NMR; 31P-NMR; cis-polyisoprene; Lactarius mushroom; Phosphorylation; Polyprenyl phosphate; trans-polyisoprene